Enhanced charge carrier transport properties in colloidal quantum dot solar cells via organic and inorganic hybrid surface passivation - Hong, J; Hou, B; Lim, J; Pak, S; Kim, B; Cho, Y; Lee, J; Lee, Y; Girard, P; Lee, S; Park, J; Morris, S; et al. (Royal Society of Chemistry, 2016)
Colloidal quantum dots (CQDs) are extremely promising as photovoltaic materials. In particular, the tunability of their electronic band gap and cost effective synthetic procedures allow for the versatile fabrication of solar energy harvesting cells, resulting in optimal device performance. However, one of the main challenges in developing high performance quantum dot solar cells (QDSCs) is the improvement of the photo-generated charge transport and collection, which is mainly hindered by imperfect surface functionalization, such as the presence of surface electronic trap sites and the initial bulky surface ligands. Therefore, for these reasons, finding effective methods to efficiently decorate the surface of as-prepared CQDs with new short molecular length chemical structures so as to enhance the performance of QDSCs is highly desirable. Here, we suggest employing hybrid halide ion along with the shortest heterocyclic molecule as a robust passivation structure to eliminate surface trap sites while decreasing the charge trapping dynamics and increasing the charge extraction efficiency in CQD active layers. This hybrid ligand treatment shows a better coordination with Pb atoms within the crystal, resulting in low trap sites and a near perfect removal of the pristine initial bulky ligands, thereby achieving better conductivity and film structure. Compared to halide ion-only treated cells, solar cells fabricated through this hybrid passivation method show an increase in the power conversion efficiency from 5.3% for the halide ion-treated cells to 6.8% for the hybrid-treated solar cells.